Litterfall and mineral return in two cork-oak forests in northeast spain - Caritat, A; Bertoni, G; Molinas, M; Oliva, M; Domínguez-Planella, A (Ann. For. Sci., 1996)
Seasonal trends in littertall and potential mineral return were studied in two cork-oak forest sites in the northeastern Iberian peninsula. The estimated average litter production was 3.9 Mg.ha-1.year -1 for one site and 4.6 Mg.ha-1.year-1 for the other; these figures are similar to those reported for holm-oak (Quercus ilex) forests in the same area. Seasonal litterfall patterns were typical of Mediterranean forest ecosystems. Leaves accounted for 46 to 78% of the total dry matter. Their annual weighted-average mineral composition was low in macronutrients (N 8-9; K 4-5; Mg 0.8-1.3; Ca 9-10 and P 0.4-1 mg.g-1) and relatively high in micronutrients such as Mn (2-2.2 mg.g-1) or Fe (0.3-0.4 mg.g-1). Minimum N and P concentrations were found during the growth period. Estimates of potential mineral return for an annual cycle were N 38-52, P 2.1-5.2, K 20-28, Ca 44-53 and Mg 5.4-5.0 kg.ha -1, depending on the site biomass and fertility.
Keywords: cork-oak; litterfall; Mediterranean forest ecosystems; nutrient cycling; Quercus suber

Estudio preliminar del crecimiento del alcornoque en la fase juvenil. - Oliva, M; Molinas, A Caritat M; Caritat, A; Molinas, M (SCIENTIA gerundensis, 1989)
Shoot elongation has been measured in two different groups of juvenil cork-oaks (Quercus suber) by means of their budding segments. One group has got 14 seedlings three years old, proceeding from a forest nursery. The other group consistes in 17 sprouts of three and one years old from a bumed cork-oak forest. Buddings segments of the three- years old seedlings show an average elongation of 4,l cm. Sprouts are more vigorous; the three years old ones have an average value of segment elongation of 6,05 cm, and the one year old ones an average value of 15,3 cm. A decrease in elongation appears along the succesive buddings
Keywords: buds; cork-oak; Quercus suber; shoot elongation; sprouts

Crecimiento longitudinal del alcornoque: segmentos y hojas - Caritat, A; Molinas, M; Oliva, M (SCIENTIA gerundensis, 1988)
This paper is directed to the basic understand of longitudinal growth of the cork-tree Quercus suber L. Branch constitution is analized through the relation of segments and leaves. To duly recognize segments in branches, an apropiate nomenclature is used. Segments length changes from 0,2 to 11,6 cm, with an average of 2,3 cm. Two kind of shoots, long and short shoots, can be distinguished. Segment elongation tend to decrease as succesive periods accumulate. No differences in segments can be related to the period of the year in which they were developed. Leaves show heteroblastic distribution. Leave lamina has an average length of 3,3 cm and is 2,O cm wide. Petiol is very constant with an average of 0,6 cm.
Keywords: branch growth; cork-tree; leaves; Quercus-suber; shoots